Effect of canagliflozin on serum electrolytes in patients with type 2 diabetes in relation to estimated glomerular filtration rate (eGFR). (September 2014) - Weir, Matthew R.; Kline, Irina; Xie, John; Edwards, Robert; Usiskin, Keith
Abstract Objective: Effects of canagliflozin, a sodium glucose co-transporter 2 inhibitor, on serum electrolytes were evaluated using pooled data from studies of patients with type 2 diabetes mellitus (T2DM). Research design and methods: Analyses were performed using two datasets, each including four placebo-controlled studies: Population 1 (N = 2215), patients with baseline estimated glomerular filtration rate (eGFR) ≥60 mL/min/1.73 m2 (mean = 89.6 mL/min/1.73 m2) and Population 2 (N = 721), patients with baseline eGFR ≥45 and <60 mL/min/1.73 m2 (mean = 53.3 mL/min/1.73 m2). Clinical trial registration: ClinicalTrials.gov, NCT01081834; NCT01106625; NCT01106677; NCT01106690; NCT01032629; NCT01064414; NCT01106651. Main outcome measures: Mean percent changes from baseline in serum electrolytes (potassium, sodium, magnesium, bicarbonate, phosphate, calcium) and outlier analyses were assessed in patients receiving canagliflozin 100 and 300 mg or placebo. Potassium changes were further evaluated based on baseline therapy with anti-hypertensive agents that interfere with potassium excretion (renin-angiotensin aldosterone system-acting agents and/or potassium-sparing diuretics). Results: Mean percent changes from baseline in potassium with canagliflozin 100 and 300 mg and placebo were 0.6%, 1.0%, and 0.5%, respectively (Week 26; Population 1); and 1.7%, 2.8%, and 0.7%, respectively (Week 18/26; Population 2). The proportion of patients who had potassium elevations meeting pre-defined outlier criteria (>5.4 mmol/L [5.4 mEq/L] and >15% increase from baseline) with canagliflozin 100 and 300 mg and placebo was 4.5%, 6.8%, and 4.7% (Population 1); and 5.2%, 9.1%, and 5.5% (Population 2). In both populations, potassium elevations were usually <6.5 mmol/L for patients treated with canagliflozin or placebo; elevations ≥6.5 mmol/L were rare but more frequent in patients taking anti-hypertensive agents that affect potassium excretion in both the canagliflozin and placebo groups. Small mean percent changes in sodium, bicarbonate, and calcium were seen across groups in both populations; small mean percent increases in magnesium and phosphate were seen with canagliflozin vs placebo, but without an increase in patients meeting outlier criteria. Adverse events related to changes in electrolytes were low across groups. Conclusions: In patients with T2DM, canagliflozin was generally associated with small mean percent changes in serum electrolytes. Infrequent episodes of potassium elevation occurred with canagliflozin 300 mg, but occurred more often in patients with reduced eGFR.